In the lion's den : Daniel Macdonald, Ireland and Empire - O'Sullivan, Niamh (Quinnipiac University Press, 2016)
Daniel Macdonald (1820-1853) is a painter who deserves to be better known. Niamh O'Sullivan's fascinating book reveals compelling new subtexts to his oeuvre and re-establishes him as a painter of national importance; it also sheds original light on the social and visual culture of Ireland in the years leading up to and during the Famine. Themes rarely visited by artists--rural violence, superstition and folklore, the Famine, and many aspects of the national character--were given spirited treatment by Macdonald who insinuated such subject matter in to the salons of metropolitan London, to venues distinctly hostile to Irish poverty, hunger and agitation. This critical biography is essential reading for anyone interested in Irish art and history.--back cover